TINGKAT SERANGAN DAN JENIS LALAT PENGOROK DAUN PADA TIGA VARIETAS LOKAL BAWANG MERAH DI LEMBAH PALU SULAWESI TENGAH - . Shahabuddin; Alam Anshary; Andi Gellang (Universitas Lampung, 2012)
Leafminer (Liriomyza sp.) is an exotic pest that currently has become a new major pest at the onion crops in Palu Valley-Central Sulawesi and it may reduce the yields up to 100%. The study was aimed to investigate the infestation level of leafminer on three local varieties of onion in Palu and to identify the leafminer species infested the onion crops. The experiment was arranged in a completely randomized design with three treatments of local onion varieties (Palu, Palasa, and Tinombo) and six replicates. The onion seeds were grown in plot of 6 x 4 m and five plants were randomely chosen as the samples to observe the percentage of pest infested and the yields. The imago of leafminer from each onion variety were collected and brought to the laboratory for identification. The results showed that the averages of infestation intensity of leafminer were 48.1 % (Palu), 47.6 % (Palasa), and 65.9 % (Tinombo) while the dry weight of bulb per 5 plant samples were 133.3 g (Palu), 120 g (Palasa), 0 g (Tinombo). The results indicated that Palu and Palasa varieties be more resistance to leafminer. The leafminer attacking onion crops in Palu is Liriomyza chinensis as indicated by some morphological characters observed.